Non-consciously processed physical activity for survival versus consciously deliberated exercise for health - Iso-Ahola, Seppo E. (Frontiers in Psychology, 2023)
ABSTRACT As facilitated by the ever-expanding brain and its nonconscious operations, humans evolved to become dependent on physical activity for their survival. But because survival in modern society relies heavily on conscious thinking, not physical activity, most people (54%) have evolved away from physical activity and become occasional exercisers. This transition from nonconscious to conscious processing prevents people from capitalizing on evolution’s wisdom for human well-being as they consciously deliberate the utility of health practices to achieve certain outcomes (e.g., weight loss). Unlike in early times, people today have a choice of not engaging in physical activity and as a result, struggle with the question whether the gains from exercising are greater than losses from not doing it, weighing positive gains and losses against negative gains and losses. Such conscious deliberations, however, can easily be overridden by resolving cognitive dissonance (e.g., “exercise is good for my health” vs. “I don’t exercise”) through excuses and rationalizations. Today’s exercise problem can only be solved by individually developing the mindset of early times of evolution when the initiation of physical activity was largely a matter of nonconscious thoughts and feelings.